2021
DOI: 10.1016/j.arrct.2021.100106
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Action Observation Therapy in the Rehabilitation of Neurologic and Musculoskeletal Conditions: A Systematic Review

Abstract: Objective To investigate the effect of action observation therapy (AOT) in the rehabilitation of neurologic and musculoskeletal conditions. Data Sources Searches were completed until July 2020 from the electronic databases Allied and Complementary Medicine Database (via OVID SP), Cumulative Index to Nursing and Allied Health Literature, Cochrane Library, EMBASE, MEDLINE, and the Physiotherapy Evidence Database. Study Selection Randomized cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 81 publications
(197 reference statements)
1
44
0
3
Order By: Relevance
“…Due to few related articles, the clinical significance of OKS and WOMAC change needs to be confirmed by more studies. Only a similar study supported action observation in improving WOMAC in patients with knee and hip arthroplasty [ 37 ]. It gave us a hint that researchers might prefer objective TUG and gait speed to subjective OKS and WOMAC.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Due to few related articles, the clinical significance of OKS and WOMAC change needs to be confirmed by more studies. Only a similar study supported action observation in improving WOMAC in patients with knee and hip arthroplasty [ 37 ]. It gave us a hint that researchers might prefer objective TUG and gait speed to subjective OKS and WOMAC.…”
Section: Discussionmentioning
confidence: 91%
“…This was consistent with articles using other movement representation techniques. Two studies observed greater ROM in the action observation group for TKA patients in acute phase [ 37 ]. Another meta-analysis showed a moderate positive effect on the knee extension and flexion of the affected leg for patients with TKA or total hip arthroplasty [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Discussion on the representation and simulation of motor acts dates back to as early as 1825 by the German philosopher and psychologist, Johann Friedrich Herbart, who proposed that the imagery of perceptual effects can elicit related movements [ 49 ]. It has since then been explored in various aspects of sports [ 50 ] and medicine [ 14 – 18 , 51 ]. Mental simulation practice has been used to rehabilitate motor deficits in various neurological [ 52 ] and musculoskeletal disorders [ 17 , 18 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has since then been explored in various aspects of sports [ 50 ] and medicine [ 14 – 18 , 51 ]. Mental simulation practice has been used to rehabilitate motor deficits in various neurological [ 52 ] and musculoskeletal disorders [ 17 , 18 , 51 ]. A systematic review and meta-analysis reported multiple positive effects on measures of physical function recovery compared with SPT in patients after TKA or THA [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…While AOT efficacy has been clearly proven for rehabilitation of central disorders [12], this approach has been significantly less studied in peripheral disorders [13][14][15]. In a randomized case-control study, Bellelli et al [13] used a 3-week combined program including conventional post-orthopedic rehabilitation (1 h a day, 6 days a week) and AOT (24 min a day, 6 days a week) in 60 patients with post-orthopedic surgery (hip arthroplasty, knee arthroplasty, hip fracture repair).…”
Section: Introductionmentioning
confidence: 99%